Discourse in Colgate Palmolive television advertisement copy: Colgate maximum cavity protection - Roslan, Nur Widad; Abdul Halim, Hazlina; Abdul Jabar, Mohd Azidan (Persatuan Linguistik Malaysia, 2019)
This study focuses on the discourse in Colgate Palmolive television advertisement copy: Colgate Maximum Cavity Protection. The objectives of the study are to identify and discuss the discourse in Colgate Palmolive video advertisement. This study will focus on the Colgate maximum cavity protection advertisement. The instrument is analysed by using the qualitative method. The Colgate advertisement copy is analysed by using Stubbs (1983) elements of discourse. Results from this study show that all the elements have helped in the process of identifying the predictability, phonotactics, intuition, analogies, grammaticality and conclusion.